Construction of corrosion resistant stainless steel mesh and the design for protecting optical window free from biofouling. (15th November 2022) - Chen, Chao; Wang, Yi; Ge, Fangfang
Abstract: Bio-fouling impedes widespread application of sensors for marine environmental monitoring. It is an issue to develop a simple and mitigating membrane fouling attachment device. In this work, an antifouling and corrosion resistant 316ss mesh combining with 3D printing was used to develop a novel device model for protecting the optical window free from biofouling under sea water. The Ag coating 800# 316ss mesh exhibited the most antifouling effect on protecting the glass not only among the different pore size, but also comparing with the naked mesh at the same pore size in natural water. However, the corrosion occurred on the Ag coating 316ss mesh in the seawater. After Al2 O3 pre-deposited on 316ss mesh prior coating Ag film, the multilayered Al2 O3 /Ag 316ss mesh were prepared successfully. To simulate experiment of protection optical window in the sea, a proper device was designed through 3D printing combined with the functional 316ss mesh, which exhibited an outstanding antifouling capacity as long as 30 days and without corrosion. This strategy demonstrated a realistic paradigm of combining 3D printing technology with the antifouling materials to design a simple and mitigating membrane fouling attachment device for commercially available sensors in the further application. Highlights: The Ag coating 800# 316ss mesh exhibited the most antifouling effect on protecting the glass. With the pre-deposited Al2 O3 prior coating Ag film, the corrosion resistance capacity of 316ss wires can be proved in the sea. 3D printing device combined with the functional 316ss mesh has an outstanding antifouling capacity as long as 30 days.